Rab7 Investigation Insights into the Existence of White Spot Syndrome Virus in Crustaceans: An In Silico Approach - Mehedi Mahmudul Hasan; M. Nazmul Hoque; Md Robiul Hasan; Mohammad Asaduzzaman; Farha Matin Juliana (Advances in Virology)
In this study, previously published Rab7 sequences from National Center for Biotechnology Information (NCBI) have been investigated from chordates, mollusks, annelids, cnidarians, amphibians, priapulids, brachiopods, and arthropods including decapods and other groups. Among decapod crustacean isolates, amino acid variations were found in 13 locations. Penaeid shrimps had variations in positions 13 (I ⟶ J), 22 (T ⟶ A), 124 (G ⟶ X), and 149 (V ⟶ X) while interestingly the freshwater prawn and mitten crab both had amino acid substitutions in positions 87 (V ⟶ C) and 95 (T ⟶ S) along with the other disagreements in amino acid positions 178 (S ⟶ N), 201 (D ⟶ E), 181 (E ⟶ D), 182 (L ⟶ I), 183 (Y ⟶ G), 184 (N ⟶ H), and 198 (A ⟶ T). Among 100 isolates of Rab7 from organisms of various phyla, mutations were observed in several positions. These mutations caused variations in hydrophobicity and isoelectric point which impact the ligand-protein binding affinity. Some common mutations were found in the organisms of the same phylum and among different phyla. Homology modeling of Rab7 proteins from different organisms was done using SWISS-MODEL and validated further by developing Ramachandran plots. Protein-protein docking showed that active residues were there in the binding interfaces of Rab7 from organisms of seven different phyla and VP28 of WSSV. Similarities were observed in the Rab7-VP28 complexes in those selected organisms which differed from the Rab7-VP28 complex in the case of Penaeid shrimp. The findings of this study suggest that WSSV may exist in different marine organisms that have Rab7 protein and transmit to crustaceans like shrimps and crabs which are of commercial importance.